Pedagogical problems encountered by teachers of English to Computer Science students in the Indonesian context - Fransisca Endang Lestariningsih; Suwarsih Madya; Joko Nurkamto (Universitas Islam Sultan Agung, 2020)
Many factors are required in order to increase the skills of English of higher education students, specifically computer science students. Of the factors, teachers play a very important role since they are the agents of change in the classrooms; not to neglect that the students are also the agents of their own changes. Using Brown’s 12 pedagogical characteristics of a good language teacher as its theory, this is a report of the first step of design-based research, practical problems encountered by teachers of English to computer science students conducted at two private universities in Indonesia. Among the 12 characteristics, knowledge of approaches to language teaching seems to be the biggest challenge that came upon the teachers. The findings of this step will subsequently be used as the bases to go further to the second cycle of design-based research, which is the development of solutions informed by existing design principles and technological innovations.